Factors Affecting the Stress Management Ability of College Students - Yazhen, Zhang; Onyon, Nitikorn; Kochasit, Sombat; Charoontham, Orasa (International Journal of Sociologies and Anthropologies Science Reviews, 2023)
Background and Aim: This study adopts the method of “building multiple linear regression model as a means of analyzing the main factors that affect the stress management ability of college students. The seven forms of stress include self-esteem stress, academic stress, interpersonal stress, adaptive stress, economic stress, love stress, and employment stress. The purpose of this study was to establish a multiple linear regression model for extracting the main factors that affect the stress management ability of college students. Materials and Methods: In this empirical study, 240 students majoring in economics and trade at the Henan Institute of Engineering were investigated. This study used a questionnaire survey given to students at the start of the semester. Data was collected and analyzed by means, standard deviation, and multiple regression analysis. Results: The investigation of seven factors that affect the stress management ability of college students found that the regression equation of stress management ability was as follows: 0.115 + (0.335*self-esteem stress) + (0.243*academic stress ) + (0.187*interpersonal stress ) + (0.124*adaptive stress ) + (0.148*economic stress ) - (0.111* love stress). Conclusion: Six factors that affected the stress management ability of students include self-esteem stress, interpersonal stress, academic stress, economic stress, love stress, employment stress, and adaptive stress.